Sex ratio of mirid populations shifts in response to hostplant co‐infestation or altered cytokinin signaling3 . Issue 1 (January 2017) - Adam, Nora; Erler, Theresa; Kallenbach, Mario; Kaltenpoth, Martin; Kunert, Grit; Baldwin, Ian T.; Schuman, Meredith C.
Abstract: Herbivore species sharing a host plant often compete. In this study, we show that host plant‐mediated interaction between two insect herbivores − a generalist and a specialist − results in a sex ratio shift of the specialist's offspring. We studied demographic parameters of the specialist Tupiocoris notatus (Hemiptera: Miridae) when co‐infesting the host plant Nicotiana attenuata (Solanaceae) with the generalist leafhopper Empoasca sp. (Hemiptera: Cicadellidae). We show that the usually female‐biased sex ratio of T. notatus shifts toward a higher male proportion in the offspring on plants co‐infested by Empoasca sp. This sex ratio change did not occur after oviposition, nor is it due differential mortality of female and male nymphs. Based on pyrosequencing and PCR of bacterial 16S rRNA amplicons, we concluded that sex ratio shifts were unlikely to be due to infection with Wolbachia or other known sex ratio‐distorting endosymbionts. Finally, we used transgenic lines of N. attenuata to evaluate if the sex ratio shift could be mediated by changes in general or specialized host plant metabolites. We found that the sex ratio shift occurred on plants deficient in two cytokinin receptors (ir CHK2/3 ). Thus, cytokinin‐regulated traits can alter the offspring sex ratio of the specialist T. notatus . Abstract : The specialist herbivore T. notatus usually has a female‐biased sex ratio on N. attenuata plants. When plants are co‐infested with the generalist Empoasca sp., the sex ratio of T. notatus progeny becomes more male‐biased. Similar effects were observed on plants deficient in two cytokinin receptors without Empoasca sp. co‐infestation.